NEMYDIS FROM THE INTESTINE OF C ORNATA - BRAVO H, MARGARITA (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1948)
Descr of C carcinophila imminuta living on the eggs of a crustacean, Araneus cribarius
ANS INST BIOL
Keywords: NEMYDIS, INTESTINE, C ORNATA; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL